The Relationship between Children's Learning Motivation and Early Childhood Learning Outcomes - Latifah Hanum Sormin (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine (1) parental support of children. (2) children's learning motivation (3) the relationship between parental support and motivation to children's learning outcomes. This research is included in quantitative research. The population of this study were all parents in the school, totaling 33 people. Determination of the sample using the saturated sample method, where all the population is sampled. Data collection techniques used in this study were observation, questionnaires or questionnaires and documentation. The data analysis technique in this study used statistical test data with SPSS ver. 23.0 for windows.